Incidence, etiology, and significance of acute kidney injury in the early post‐kidney transplant period. Issue 1 (23rd November 2015) - Panek, Romuald; Tennankore, Karthik K.; Kiberd, Bryce A.
Abstract: Little is known about the incidence, causes, and significance of acute kidney injury (AKI) in the early transplant period. This study used a definition as >26 μmol/L increase in creatinine within 48 h or >50% increase over a period >48 h. In 326 adult consecutive recipients of a solitary kidney transplant from 2006 to 2014 followed at this center, 21% developed AKI within the first six months. Most etiologies were CNI toxicity (33%) or unknown (26%), whereas acute rejection accounted for 17% and urinary tract obstruction for 10%. Those with AKI had a significantly lower glomerular filtration rate (GFR) at one‐yr post‐transplant (adjusted beta coefficient −5.5 mL/min/1.73 m 2, 95% CI: −10.4, −0.7, p = 0.025) in a multivariable linear regression model. However, the AKI definition missed 6 of 19 episodes of acute rejection and 4 of 10 episodes of urinary tract obstruction. When acute rejection (including those that did not satisfy AKI criteria) was included in the model, other causes of AKI were not significantly associated with GFR at year 1. Although AKI, using current criteria, is likely to be a significant predictor of later outcomes, important causes are missed and the criteria are not sensitive for clinical decision‐making.